The Influence of Abdominal Circumference and Body Mass Index On Hypertension - anggraeni, Ratih; Marbun, Romauli Anna Teresia; Siagian, Hartika Samgryce; Lubis, Amelia Hasana (Jurnal FARMASIMED (JFM), 2024)
The Body Mass Index (BMI) value is used to determine the body composition value, calculated using a formula involving height and weight. Increasing body weight will affect the size of the stomach circumference. One indicator of BMI that can identify the risk of morbidity due to increased body weight is the measurement of the size of the abdominal circumference. If there is an increase in BMI, the risk of developing hypertension and other heart diseases also increases. Hypertension is when a person's blood pressure exceeds normal (120/80mmHg). This research was conducted to analyze the influence of BMI and abdominal circumference on hypertension symptoms using analytical observation. Random sampling was taken from the USU Faculty of Medicine student population with the criteria of having a history of heart disease, a history of metabolic disease, taking heart medication, and being an athlete. Respondents had their height and weight measured, their BMI values were calculated, then their abdominal circumference, and their blood pressure. The results showed that there was an influence between BMI and abdominal circumference on symptoms of hypertension. There was a significant correlation between BMI and systole (p=0.000) and diastole (p=0.014) as well as a moderate correlation coefficient for systole (r=0.466) and diastole (r=0.340). There is a correlation between abdominal circumference and systole (p=0.000) and diastole (p=0.038) and a moderate level correlation coefficient with systole (r=0.480) and diastole (r=0.289). It can be concluded that there was an influence of BMI and LP on hypertension.